Public Ownership and Institutional Ownership on Firm Value Through Financial Performance - Abdul Rahman; Arjang Arjang; Nisma Iriani; Hanadelansa (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study intends to evaluate and determine the influence of public ownership and institutional ownership on company value by analyzing the financial performance of manufacturing companies listed on the Indonesia Stock Exchange in the Metal Subsector and similar industries (IDX) from 2019 to 2021. Determination of the sample using a purposive sampling technique to identify 14 companies using secondary data. To test the hypothesis, Eviews 12 was utilized to conduct a panel data analysis. The data analysis included descriptive statistics, normality tests, autocorrelation, heteroscedasticity, and determination coefficient (R Square). The results indicate that public and institutional ownership positive and statistically significant impact on financial performance. Public and institutional ownership has a favorable and significant effect on the value of a company. Financial Performance has a positive and substantial impact on the value of a company. Public and institutional ownership has a favorable and considerable effect on the value of a company as measured by its financial performance. We recommend to investors that, if they wish to invest, they get information as soon as possible so that there is no asymmetry of knowledge present when making investment selections. Firms should disclose information about their financial accounts so that investors may quickly acquire the required information and avoid losses for investors and the company itself. This study mainly utilizes metal subsector manufacturing companies; thus, it is hoped that future research will be able to incorporate companies from other industries.